PENGARUH SALES GROWTH DAN ARUS KAS TERHADAP FINANCIAL DISTRESS PADA PT GARUDA INDONESIA (PERSERO) PERIODE TAHUN 2013-2022 - Triana Ayu Safitri, Indah; Astuti, Widia (Journal of Research and Publication Innovation, 2024)
This research aims to find out whether Sales Growth and Cash Flow have an effect on Financial Distress at PT Garuda Indonesia Persero for the 2013-2022 period. This research uses a descriptive method with a quantitative approach. The population used in this research is the financial report of PT Garuda Indonesia Persero, while the sample used is the financial report in the form of a profit and loss report and balance sheet at PT Garuda Indonesia Persero for the 2013–2022 period. The data analysis method uses descriptive statistical analysis tests, classical assumption tests, linear regression tests, coefficient of determination tests, and hypothesis tests with the help of the SPSS version 26 program. Sales Growth is concluded to have an influence on Financial Distress based on the results of hypothesis testing. Sales Growth has a t count of 3.083 while t table is 2.365. The significant value of 0.018 is smaller than 0.05. Because the calculated t value > t table. Cash Flow has a calculated t of 0.737 while the t table is 2.365. The significant value of 0.485 is greater than 0.05. The calculated t value is < table so it can be concluded that H0 is accepted, meaning it can be concluded that partially, Cash Flow has no effect on Financial Distress. Meanwhile, based on table 4.13, it is known that the calculated F is 5,690 while the F table is 4.74. The significant value of 0.034 is smaller than 0.05. The calculated F value > F table so it can be concluded that H0 is rejected, meaning that simultaneously there is a significant influence of Sales Growth and Cash Flow on Financial Distress at PT Garuda Indonesia Persero for the 2013-2022 period.